2021
DOI: 10.1063/5.0033707
|View full text |Cite
|
Sign up to set email alerts
|

Large anomalous Hall angle in a topological semimetal candidate TbPtBi

Abstract: The magnetotransport properties in antiferromagnetic half-Heusler single crystals of TbPtBi, a magnetic-field-induced topological semimetal with simple band structure, are investigated. We found that a nonmonotonic magnetic field dependence of the anomalous Hall resistivity in a high magnetic field (B>7T), which come from the change of band structure induced by the Zeeman-like splitting when applying the external magnetic field. The experiment results show that credible anomalous Hall resistivity and conductiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
3
9
1
Order By: Relevance
“…Previous studies suggest that large anomalous Hall angle of TbPtBi results from large net Berry curvature induced by Weyl points or anti-crossing of spinsplit bands. [25][26][27][28] In our study, as suggested by DFT calculation results shown in Figure 1c, the large net Berry curvature at Fermi level is mainly contributed by Weyl points. To further confirm this point, we performed measurement on longitudinal magneto-resistance (LMR) (Figure 3a,b) and planar Hall resistance (PHE) (Figure 3c,d).…”
Section: Topological Band and Bipolar Effect Enhanced S Yx (B)supporting
confidence: 71%
See 2 more Smart Citations
“…Previous studies suggest that large anomalous Hall angle of TbPtBi results from large net Berry curvature induced by Weyl points or anti-crossing of spinsplit bands. [25][26][27][28] In our study, as suggested by DFT calculation results shown in Figure 1c, the large net Berry curvature at Fermi level is mainly contributed by Weyl points. To further confirm this point, we performed measurement on longitudinal magneto-resistance (LMR) (Figure 3a,b) and planar Hall resistance (PHE) (Figure 3c,d).…”
Section: Topological Band and Bipolar Effect Enhanced S Yx (B)supporting
confidence: 71%
“…Due to large net Berry curvature at the Fermi level, TbPtBi exhibits large anomalous Hall conductivity and anomalous Hall angle (Figure S3, Supporting Information), which further enhances total Hall angle (Figure 1d) and are consistent with previous reports. [25][26][27][28] Moreover, the maximum total Hall angle of ≈3 at 2 K and 14 Tesla is larger than previous reports [25][26][27][28] and some other magnetic topological materials, such as Co 3 Sn 2 S 2 , Mn 3 Ge, and GdPtBi. [29][30][31] Based on Mott formula and linear response equation, the transverse thermopower can be expressed as [32] In the case where Hall angle is energy dependent, taking a first-order approximation of above formula, the transverse thermopower can be rewritten as…”
Section: Unique Features Of Tbptbi For High Te Performancecontrasting
confidence: 54%
See 1 more Smart Citation
“…Small anomalous Hall angles were obtained compared with the Co2MnGa Heusler compound, which has been widely studied in the literature and for which a large 𝜃 𝐴𝐻𝐸 of ~10 % have been reported [50][51][52]. This can be explained by the weaker spin-orbit coupling in the Co2MnSi compound linked to its lower magnetocrystalline anisotropy compared to Co2MnGa.…”
Section: Data Availabilitymentioning
confidence: 85%
“…We estimated anomalous Hall angle θ AHA (represents the relative contribution of the anomalous Hall current with respect to the longitudinal current) of Fe 3 Sn 2 thin films from the slope of σ AHE xy vs. σ xx . 62 The transverse Hall conductivity σ xy was calculated by using the formula: σ xy = ρ yx /( ρ xx 2 + ρ yx 2 ). We found more than one order of magnitude higher anomalous Hall angle, θ AHA = 0.60° in the Pt/Fe 3 Sn 2 thin film as compared to θ AHA = 0.04° in the Ta/Fe 3 Sn 2 thin film.…”
Section: Resultsmentioning
confidence: 99%